2021
DOI: 10.3389/fonc.2021.647179
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Death After Colorectal Cancer Diagnosis: A Population-Based Study

Abstract: Background: Non-cancer causes of death in patients with colorectal cancer (CRC) have not received much attention until now. The purpose of the current study is to investigate the non-cancer causes of death in patients with CRC at different periods of latency.Methods: Eligible patients with CRC were included from the Surveillance, Epidemiology, and End Results (SEER) database, and standardized mortality ratios (SMRs) were calculated using the SEER*Stat software 8.3.8.Results: A total of 475,771 patients with CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…Hence, they are more vulnerable to infections and other diseases. Furthermore, Feng et al (21) described that 51.3% of their observed population had died colorectal cancer-related, which is similar to our rate of 46% directly cancer-associated deaths and 38% had died unrelated to cancer. Wang et al ( 22) describe a lower rate of 28% non-cancer-related death, closer to our pathologically confirmed rate of 25%.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Hence, they are more vulnerable to infections and other diseases. Furthermore, Feng et al (21) described that 51.3% of their observed population had died colorectal cancer-related, which is similar to our rate of 46% directly cancer-associated deaths and 38% had died unrelated to cancer. Wang et al ( 22) describe a lower rate of 28% non-cancer-related death, closer to our pathologically confirmed rate of 25%.…”
Section: Discussionsupporting
confidence: 89%
“…As in the general population, infections played another major part in the death of our patients (20) and were the second most common cause of death combined with underlying cancer and also the most common major missed diagnosis. Two population analyses showed a similar result; one analysis of colorectal cancer patients by Feng et al (21) and one of renal cell carcinoma patients by Wang et al (22). They showed that although cancer was still the most common cause of death, Findings were categorized by a pathologist as cancer-related, as a combination of cancer and other disease or as unrelated to the underlying cancer.…”
Section: Discussionmentioning
confidence: 88%
“…[9][10][11][12] Recent studies suggested that cardiovascular death would probably outweigh that of cancer death, particularly for young patients and colorectal cancer patients survived more than 10 years. 13,14 However, it has not received enough attention. Moreover, it's still unclear whether long-term cardiovascular mortality risk will outweigh cancer mortality risk in other cancer patients, and when does cardiovascular mortality risk begin to outweigh cancer mortality risk.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, inflammation is thought to play an important role in the underlying mechanism of fatigue in cancer patients (15). Better adherence to the WCRF/AICR lifestyle recommendations for cancer prevention on physical activity, body weight and healthy diet may potentially impact fatigue by attenuating systemic inflammatory processes (50)(51)(52). However, the potential mediating role of inflammation needs to be confirmed at present.…”
Section: Lifestyle and Fatigue In Stage I-iii Colorectal Cancermentioning
confidence: 99%
“…However, it has been shown that healthy lifestyle changes can have a positive effect on QOL in CRC patients (49). Furthermore, cardiovascular disease is a major cause of death after CRC diagnosis (50). Healthy lifestyle changes can play an important role in lowering the risk of death from cardiovascular disease.…”
Section: Implications For Clinical Practicementioning
confidence: 99%